Crossbreeding heifers performance in different reproductive stage - Marques, Jair de Araújo; Prado, Ivanor Nunes do; Maggioni, Daniele; Rigolon, Luiz Paulo; Caldas Neto, Saul Ferreira; Zawadzki, Fernando (Semina: Ciências Agrárias, 2010)
Twenty-one crossbreeding heifers (½ Nelore vs ½ Aberdeen Angus) with about 307.90 kg of live weight and eighteen months of age were used in a complete randomized design with three treatments and seven repetitions. The treatments were: control heifers, ovariectomized animals and with fifty gunshot spheres in uterine corn. The heifers were fed with 50% of corn silage and 50% concentrated. The feed intake was about 2,5% weight live in dry matter. The heifers gunshot treatments showed was bigger weight gain than the heifers ovariectomized treatments and this more weight gains what control heifers treatments. There was not difference in carcass yield and fat covering amongst treatments. The hematocrito increased in three heifers groups in the first collection (before) for the second collection (after treatments). However, the increase was superior (P < 0,05) in the control heifers group.